Introduction - Léa Linconstant; Fleur Beauvieux; Efigies Aix-Marseille (Glad!)
As an offspring of a collaboration between the members of EFiGiES Aix-Marseille and the editorial committee of GLAD!, this thematic issue is dedicated to the dialectical link between centre and margins, and aims to study how this contributes to (de)construct sexual norms. The papers not only question the tension between margin and centre or between dominant and dominated, but also focus on “grey areas” of what can be considered as marginal or not. These relations between norms and margins, sexual norms and domination relationships are discussed through narratives collected from margins, as well as the silences marginality produces, especially regarding sexual violence. Multiplying the analysis scales sheds light on various speeches questioning the relations between norm and margin. The issue also includes a varia section as well as chronicles, news in the gender and language field and book reviews.